Vertical Video Trends Among Amateur Digital Platform Users as an Alternative for Film Production - Retno Mustikawati; Ghalif Putra Sadewa; Muhammad Alvin Fadholi (Journal of Urban Society's Arts, 2022)
The Vertical Video Syndrome expression adequately represents the spread of the production process and projection of amateur digital content in vertical format. For smartphone users, the vertical is the king. All components of digital life make users subconsciously hold their phones vertically on various occasions. Penetration after penetration is carried out, from flexibility and artificial intelligence, to private viewing rooms that move dynamically. As a new starting point in quite an extended period, the vertical video gives birth to a glimmer of hope in a film atmosphere that seems exclusive and rigid. However, problems have arisen as user demands have increased and smartphones have become sociocultural necessity over the last decade. With a vertical screen, people are used to spending time watching video shows, including recording all their activities. Because of that, there is a big challenge for filmmakers to see the opportunities that exist. The vertical format creates a narrow, elongated reading space. The camera movement, which used to use action from left to right, now switches from top to bottom. Subjects in vertical formats are also forced to submit to limited reading space. In conventional films, close-ups can isolate the field of view while at the same time emphasizing facial expressions. But not vertically because it will bring out a different density; what arises is not a close-up but a big close-up and even an extreme close-up. As a result, this gives motivation and a different meaning visually. It would be a lie if this didn't fall into the challenges to be solved. The field of view gets more complicated. The vertical concept encourages creators to get out of the conventional mindset. Likewise, with the actors involved, the vertical format provides a more challenging exploration of expressions and gestures. This research uses qualitative methods in collecting data and utilizes a lot of current literature. The research results are in the form of knowledge and recommendations regarding the packaging and distribution of film production in a vertical format. Tren Video Vertikal di Antara Pengguna Platform Digital Amatir sebagai Alternatif Produksi Film. Sindrom Video Vertikal, ungkapan itu cukup mewakili merebaknya proses produksi dan proyeksi konten digital amatir berformat vertikal. Bagi pengguna smartphone, vertikal adalah raja. Seluruh komponen kehidupan digital membuat pengguna secara alam bawah sadar memegang telepon secara vertikal dalam beragam kesempatan. Penetrasi demi penetrasi dilakukan, fleksibilitas, kecerdasan buatan, hingga ruang tonton privasi yang bergerak dinamis. Sebagai titik pijak baru dalam kurun waktu yang cukup panjang, video vertikal melahirkan secercah harapan dalam suasana perfilman yang terkesan eksklusif dan kaku. Namun, persoalan pun muncul, di kala tuntunan pengguna semakin tinggi dan smartphone menjadi kebutuhan sosiokultural sejak satu dekade terakhir. Dengan layar vertikal, orang terbiasa menghabiskan waktu untuk menonton tayangan video termasuk merekam segala aktivitasnya. Karena itulah, muncul tantangan besar bagi pembuat film guna melihat peluang yang ada. Format vertikal mencipta ruang baca yang menyempit memanjang. Memindahkan pergerakan kamera yang terbiasa memanfaatkan pergerakan dari kiri ke kanan, kini beralih dari atas ke bawah. Subjek pada format vertikalpun dipaksa untuk tunduk pada ruang baca yang terbatas. Pada film konvensional, close-up sudah mampu mengisolasi ruang pandang sekaligus mempertegas ekspresi wajah. Namun tidak pada vertikal karena akan memunculkan kepadatan yang berbeda, yang timbul bukan close-up melainkan big close-up bahkan extreme close-up. Alhasil ini memberi motivasi dan makna yang berbeda secara visual. Suatu kebohongan jika ini tidak masuk dalam kategori tantangan yang harus dipecahkan. Ruang pandang menjadi sedikit lebih rumit. Konsep vertikal benar-benar mendorong kreator untuk keluar dari pola pikir konvensional. Begitu pula dengan aktor yang terlibat, format vertikal memberikan tantangan eksplorasi yang lebih pada ekspresi dan gerak tubuh. Penelitian ini menggunakan metode kualitatif dalam mengumpulkan data dan memanfaatkan banyak literatur saat ini. Hasil penelitian berupa pengetahuan dan rekomendasi tentang pengemasan dan distribusi produksi film dalam format vertikal.